Institutional development method as a tool of improving the activities of public administration. Case of local government strategies - Bober, Jarosław (Journal of Public Governance, 2008)
The main aim of the article is to describe the institutional development method (ID method), which, in principle, serves to improve the activities of public administration, and an example of its practical application. The article consists of five parts. Part one outlines the fundamental nature of the institutional development method. Part two contains the results of evaluation of management quality in local authorities conducted using the method in question. The two subsequent parts of the article are devoted to the practical verification of the method, with the first presenting the approach to strategy adopted in the ID method, and the second one analysing the changes in the area of strategic management in 11 local authorities that have tested the method under discussion. The article closes with conclusions concerning the evaluation and application of solutions proposed by the ID method for strategic planning at local government level.